Effect of Nigella sativa Oil on Pyruvate Kinase Activity in Kidney Tissue in Doxorubicin-Treated Rats: ADME Predictions and Molecular Docking Studies - Uslu, Harun; Kaya, Emre; Yilmaz, Seval (My University, 2025)
This study aimed to investigate the effect of Nigella sativa oil (NSO) on pyruvate kinase (PK) after Doxorubicin (DOX) application in kidney tissue. When the DOX group was compared with the control group, a decrease in PK activity was found, and a significant difference was found in PK activity. While no statistically significant difference was found between the group administered only NSO and the control group, it was determined that PK activity increased statistically significantly in the group administered NSO together with DOX compared to the DOX group, and the values approached control group values. According to recent studies, in silico molecular docking studies and ADME predictions were performed by selecting the compounds in the highest amounts in the fixed oil and essential oil obtained from NSO. Using molecular docking, we looked into how NSO affected PK. Some selected NSO components were shown to interact similarly with the cocrystal ligands of PK. Molecular docking studies showed that Palmitic acid (c) and Thymoquinone (e) were one of the selected compounds with the best pose on the PK, for fixed and essential oils respectively. It was estimated that NSO fixed oil components would inhibit at PK nanomolar level (4.57 nm-17.72 nm) and NSO essential oil components would inhibit at PK micromolar level (52.05 µM-255.92 µM). Considering ADME predictions Oleic acid (b), Palmitic acid (c), p-Cymene (d), Thymoquinone (e), and Carvacrol (f) had good pharmacokinetic profiles, but Linoleic acid (a) did not find drug-likeness properties.
Keywords: Molecular docking; doxorubicin; pyruvate kinase; ADME; nigella sativa oil